Removal Dye By Adsorption Onto Pineapple Peel Powder - Teong, Hui Yin (Penerbit Universiti Malaysia Perlis, 2011)
The adsorption behavior of methylene blue on pineapple peel powder was studied on batch modes of operation. The operation parameters investigated including initial dye concentration (60-100mg/L), contact time, pH of solution (2-12), adsorbent dose (1-5g/L). The adsorption was favorable at higher pH. The experimental data were analyzed using Langmuir and Freundlich isotherm model. Langmuir and Freundlich isotherm model constants and correlation coefficients were calculated. The Langmuir isotherm model fits the data very well for the methylene blue on pineapple peel powder. Pseudo-first-order and pseudo-second-order kinetic were used to analyze the kinetic data. From the kinetic studies the rate constant values for the adsorption process was calculated. Kinetic studies showed that the adsorption followed a pseudo-second-order model. The pseudo-second-order kinetic data fit well on whole system for dye studies. UV-vis spectroscopy was used. Removal of MB from aqueous solutions by adsorption on pineapple peel powder has been found to be useful for controlling the water pollutions due to dyes.